2021
DOI: 10.3390/ijerph18115534
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Cognition and Attitude with Eco-Friendly Menstrual Products by Consumer Lifestyle

Abstract: With rapid technology developments and the convenient and fast pace of life in recent years, many people are using disposable products, which cause environmental and ecological damages. A variety of eco-friendly menstrual products have been launched on the market, and “menstrual pads” now have a large market share in Taiwan’s menstrual product industry. This study interviewed experts and collected questionnaires for qualitative and quantitative investigation and analysis. The results show that women have posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Participants thought it was comfortable, cheaper in the long-term, did not smell bad (like non-reusable products do) and it allowed for women and PWM to know more about their menstruation and body. The fact that the menstrual cup is an environmentally-friendly option was another reason for participants to use it, as other research has found [ 32 ]. Previous evidence also supports our findings on the acceptability of the menstrual cups as a more comfortable and preferred product, compared to non-reusable products [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants thought it was comfortable, cheaper in the long-term, did not smell bad (like non-reusable products do) and it allowed for women and PWM to know more about their menstruation and body. The fact that the menstrual cup is an environmentally-friendly option was another reason for participants to use it, as other research has found [ 32 ]. Previous evidence also supports our findings on the acceptability of the menstrual cups as a more comfortable and preferred product, compared to non-reusable products [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women face logistical challenges in storing and transporting menstrual products as secrecy around purchasing sanitary items, overcrowded housing, living across multiple residences, high nancial costs, lack of privacy for safe keeping of personal items, su cient female-friendly infrastructure (e.g., working toilets, accessible disposal facilities, privacy) [5]. The MHH content and material should be dealt with the sensitivity and should be made available to all genders.…”
Section: Studies Focused On Awareness About Menstruation and Menstrua...mentioning
confidence: 99%
“…Additionally, vending machines that provide free MHH products may improve access for girls while in school. Still, more evidence is needed to inform knowledge of the effectiveness and implementation of the strategy before scaling up [5]. It is assumed that young girls learn about their menstruation from their mothers.…”
Section: Studies Focused On Awareness About Menstruation and Menstrua...mentioning
confidence: 99%
See 2 more Smart Citations